Photosensing properties of pentacene thin film transistor with solution-processed silicon dioxide/graphene oxide bilayer insulators - Karteri, Ibrahim; Karatas, Sukru; Yakuphanoğlu, Fahrettin (Springer, 2016)
In this paper, the photoresponse properties are investigated for the pentacene thin film transistor with solution-processed silicon dioxide/graphene oxide (GO) bilayer insulators. The GO is synthesized by a modified Hummers method. It is determined that the electrical characteristics and photosensing parameters of the thin film transistor under dark and white light illuminations. The mobility A mu value (3.752 x 10(-1) cm(2)/Vs) of the thin film transistor under dark is lower than that of the value (4.557 x 10(-1) cm(2)/Vs) under 100 mW/cm(2) illumination. The interface trap density of the transistor is reduced with the rise various illuminations. The photoresponse of the thin film transistor with dioxide/GO bilayer insulators in the on state is lower than that of the thin film transistor in the off state. The photoresponse characteristics indicate that the pentacene thin film transistor with solution-processed silicon dioxide/GO bilayer insulators exhibits a phototransistor characteristic.
Keywords: Field-Effect Transistors; Graphene-Oxide; Dielectric Layer; Performance; Mobility